The Effect Of Teacher Well-Being, Teacher Competency, And Teacher Commitment To Improving School Quality - Dian Hidayati; Arief Kurniawan; Ibnu Asakir (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
School quality is inseparable from the role of teachers, supported by teacher well-being, competence, and commitment. For this reason, this research’s design is quantitative research, using ex-post-facto with a population of 456 teachers and 112 research samples. Instrument validation was performed through expert judgment and tested using the Rasch Model. Data were then collected through questionnaires distributed using a google form, and data analysis testing consisted of (1) instrument data analysis using the Rasch Model by testing person reliability, item reliability, and instrument bias testing; (2) the analysis of data results through prerequisite tests and hypothesis testing, utilizing multiple linear regression with SPSS. The results showcased that (1) there was a simultaneous positive and significant effect between teacher well-being, teacher competence, teacher commitment, and school quality of 0.000 <0.05. (2) There was a positive and significant effect of teacher well-being on school quality of 0.009 <0.05. (3) There was a positive and significant effect of teacher competence on school quality of 0.014 <0.05. (4) There was a positive and significant effect of teacher commitment on school quality of 0.000 <0.05. In addition, this study's findings imply that teacher competence and well-being had the most influence on school quality compared to teacher commitment. Second, 42.4% of school quality was influenced by the teacher's well-being, competence, and commitment. Based on these findings, increasing teacher commitment through strategic programs expected to improve schools' quality is necessary.